2021
DOI: 10.1097/oi9.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Expanded use of tranexamic acid is safe and decreases transfusion rates in patients with geriatric hip fractures

Abstract: Objectives: To determine the effect of a standardized tranexamic acid (TXA) protocol on red blood cell transfusions and adverse events in fragility hip fracture patients. Design: Retrospective cohort study. Setting: Academic Tertiary Care Center. Patients/Participants: Series of 209 patients with fragility hip fractures treated operatively from April 1, 2019 to September 30, 2019. Intervention: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In 1976, a study reported the use of TXA in orthopedic treatment to reduce bleeding in patients [ 20 ]. Recent literature confirms that surgical trauma leads to the release of tissue-type fibrinogen activators, which degrades fibrin and multiple coagulation factors, decreasing their plasma levels and activity [ 21 ]. The mechanism of action of TXA is to prevent fibrin degradation by fibrinolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, a study reported the use of TXA in orthopedic treatment to reduce bleeding in patients [ 20 ]. Recent literature confirms that surgical trauma leads to the release of tissue-type fibrinogen activators, which degrades fibrin and multiple coagulation factors, decreasing their plasma levels and activity [ 21 ]. The mechanism of action of TXA is to prevent fibrin degradation by fibrinolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were determined by TXA contraindications in drug information literature. 1 In addition to patients with an allergy to TXA and impaired renal function, patients at highest risk of venous or arterial thrombotic disease were excluded. This category includes patients with a history of a vascular event within the last year or active malignancy.…”
Section: Methodsmentioning
confidence: 99%
“…If medically cleared, all patients were taken to the operating room within 24 hours of admission. 1 For patients that were eligible for the 4-dose regimen but had not received the initial admission TXA doses, due to either protocol deviations, misunderstandings by different care teams, or random errors, all these patients were still given 1-g of TXA at the time of surgical incision followed by 1 g 3 hours later. Similarly, there were patients that were deemed ineligible for the 4-dose TXA protocol due to the aforementioned contraindicated comorbidities, but some respective care teams proceeded with an abbreviated two-dose TXA of 1-gram of TXA at the time of surgical incision followed by 1 g 3 hours later for these patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations